SUSTAINABILITY-BASED WAKAF DEVELOPMENT STRATEGY : A CASE STUDY OF MEKAR REJO VILLAGE, SIMALUNGUN REGENCY - Dinda Amalia; Imsar; Nursantri Yanti; Maryam Batubara (Ekonomi Islam, 2026)
Research aims: This study aims to analyze the development of educational waqf in Mekar Rejo Village, identify the structural impediments hindering its sustainability, and formulate a robust development strategy. Design/Methodology/Approach: This study employs a qualitative case study design, data were collected through in-depth interviews, field observations, and document analysis. Key informants included waqf heirs, managers, school administrators, village officials, and beneficiaries. Data validity was ensured through rigorous triangulation, member checking, and audit trails. Research findings: The findings demonstrate that educational waqf in Mekar Rejo Village has yielded substantial social dividends, particularly by enhancing access to Islamic education and generating local employment opportunities. However, its administration is beset by several structural impediments, notably a 'nazhirless' condition characterized by the absence of a formally appointed nazhir as well as a lack of legal certification through a waqf pledge deed. Furthermore, the unproductive utilization of cash waqf and a profound reliance on external funding remain critical concerns. Consequently, the waqf mechanism has yet to materialize as a self-sustaining economic and institutional framework. Theoretical Contribution/Originality: This study enriches the existing literature by elucidating the phenomenon of 'nazhirless waqf', which has received limited attention in previous studies that generally assume the presence of formal waqf governance structures. Furthermore, it advances the field by integrating multifaceted sustainability perspectives into waqf governance frameworks specifically at the grassroots or village level. Practitioners/Policy Implications: The study advocates for a strategic, phased development framework to ensure long-term viability. This includes the formalization of nazhir appointments, the reinforcement of legal status through official certification, and the rigorous separation of waqf assets from institutional operational funds. Furthermore, it suggests a gradual transition of cash waqf into a productive endowment fund, complemented by robust initiatives to enhance transparency and waqf literacy. These strategies offer a scalable practical model for improving community-based waqf governance in similar rural contexts. Research Limitations/Implications: As a single-site case study, the findings of this research may have limited generalizability to broader geographical areas. Additionally, this study focuses on governance structures and does not quantitatively evaluate specific educational outcomes. Future research is encouraged to conduct comparative studies and incorporate quantitative methods to evaluate the impact of sustainable waqf management.